The role of the density profile in the ASDEX-Upgrade pedestal structure. (18th October 2016) - Dunne, M G; Potzel, S; Reimold, F; Wischmeier, M; Wolfrum, E; Frassinetti, L; Beurskens, M; Bilkova, P; Cavedon, M; Fischer, R; Kurzan, B; Laggner, F M; et al.
Abstract: Experimental evidence for the impact of a region of high density localised in the high-field side scrape-off layer (the HFSHD) on plasma confinement is shown in various dedicated experiments on ASDEX Upgrade (AUG). Increasing main ion fuelling is shown to increase the separatrix density and shift the density profile outwards. Predictive pedestal modelling of this shift indicates a 25% decrease in the attainable pedestal top pressure, which compares well with experimental observations in the gas scan. Since the HFSHD can be mitigated by applying nitrogen seeding, a combined scan in fuelling rate, heating power, and nitrogen seeding is presented. Significant increases in the achievable pedestal top pressure are observed with seeding, in particular at high heating powers, and are correlated with inward shifted density profiles and a reduction of the HFSHD and separatrix density. Interpretive linear stability analysis also confirms the impact of a radially shifted pressure profile on peeling-ballooning stability, with an inward shift allowing access to higher pressure gradients and pedestal widths.